Seeds of power environmental injustice and genetically modified soybeans in Argentina - Leguizamón, Amalia, 1979- (Duke University Press, 2020)
"SEEDS OF POWER explores the adoption and implementation of genetically modified (GM), herbicide-tolerant soybeans in Argentina, arguing that GM crops are not a technological solution promoting sustainable development, but rather, a tool of power that serves to create quiescence and consent in the face of environmental injustice. As the third largest global grower and exporter of GM crops, Argentina serves as an important case study to highlight the resulting agrochemical spraying, deforestation, and violent displacement of peasant and indigenous populations. Amalia Leguizamón explores the emergence of and obstacles to collective environmental action over the past decade. Leguizamón employs the analytical framework of "synergies of power" to describe the actors that create and legitimate human suffering, social inequality, and environmental degradation, while also working to diminish the power of social movements against extractivism. Chapter 1, "The Roots of the Soy Model," traces the timeline for the political economy of soybean extractivism in Argentina, focusing on the mechanisms of social control and violence that have kept it in place for so long. In chapter 2, "Revolution in the Pampas," Leguizamón situates the current period of relative material abundance, replete with trickle-down profits and economic redistribution, as coming after a period of major crisis and scarcity. Chapter 3, "The Elephant in the Field," exposes the reality that the risks of agrochemical exposure is both known and ignored in the rural communities of the Pampas. In chapter 4, "Against the Grain," Leguizamón highlights the communities that actively organized to protest against environmental injustice, protests led mainly by women, peasants, and indigenous peoples"--